CEA-, Her2/neu-, BCRP- und Hsp27- positive Mikropartikel bei Brustkrebspatientinnen - Liebhardt, Susanne; Ditsch, Nina; Rank, Andreas; Jeschke, Udo; Koch auf Rohrbach, Franz von; Friese, Klaus; Toth, Bettina (Geburtshilfe und Frauenheilkunde, 2009)
Thieme E-Books & E-Journals
Gesehen am 15.03.2023